2017
DOI: 10.1007/s13187-017-1203-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Training via Short Messages and Group Training on Level of Knowledge and Practice of Middle-Aged Women About Breast Cancer Screening Tests

Abstract: This study is aimed to compare the effect of two methods of short messages and group training on level of knowledge and practice of middle-aged women about breast cancer screening procedures. This clinical trial study was done on 210 women aged 40-60 years in Mahshahr city, Iran. Eligible middle-aged women were randomly assigned in two groups of short message (n = 105) and group training (n = 105). Data collected through a questionnaire which included three parts (demographic, knowledge and practice of women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Wood et al also reported that using SMS messages is beneficial in enhancing perinatal education for midwives 24 . Conversely, Naserian et al and Gill et al revealed that using SMS messages as a training tool was not an effective approach to improve knowledge levels in medical education 20,31 . One possible explanation for this might be the differences in studies regarding sample size, participants, outcome measures, potential bias in scores, or the quality of the research methodology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wood et al also reported that using SMS messages is beneficial in enhancing perinatal education for midwives 24 . Conversely, Naserian et al and Gill et al revealed that using SMS messages as a training tool was not an effective approach to improve knowledge levels in medical education 20,31 . One possible explanation for this might be the differences in studies regarding sample size, participants, outcome measures, potential bias in scores, or the quality of the research methodology.…”
Section: Discussionmentioning
confidence: 99%
“…24 Conversely, Naserian et al and Gill et al revealed that using SMS messages as a training tool was not an effective approach to improve knowledge levels in medical education. 20,31 One possible explanation for this might be the differences in studies regarding sample size, participants, outcome measures, potential bias in scores, or the quality of the research methodology. In addition, there is a need for more high-quality RCTs on text messaging in enhancing the cardiac arrhythmia interpretation skills of ICU nurses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested the use of smartphones in promoting health knowledge, behaviors, and outcomes [ 23 , 24 ]. Using smartphone applications has been reported to have a positive effect on the performance of BSE among females [ 25 ]. Health education based on the novel educational techniques in the field of BSE can enrich the quality of education, increase women's awareness regarding BSE, and change their attitudes and scientific skills, so that they accept BSE as a health habit [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an effective tool and intervention method, a series of studies have revealed the positive effects of sending health information by one-way or an interactive way for pre-exposure prevention [4]. SMS can help people manage their health [5,6] and prevent disease [7,8]. In particular, due to its cheaper price, it is feasible to conduct public health interventions in low-and middleincome countries [9].…”
Section: Literature Review: Sms Application Areasmentioning
confidence: 99%